SPATIAL ANALYSIS OF MEAN ANNUAL TEMPERATURE AND RAINFALL FOR THESÃO PAULO STATE (BRAZIL) - VIEIRA, SIDNEY R.; CAMARGO, MARCELO B. P. DE; SIQUEIRA, GLÉCIO M. (Revista Brasileira de Engenharia de Biossistemas, 2009)
The objective of this study was to analyze the spatial variability of mean annual temperature andrainfall for São Paulo State (Brazil). Data from 416 meteorological stations measured from 1936 to1992 were analyzed for two climatic parameters (mean annual temperature and mean annualprecipitation). The data were analyzed using descriptive statistics and geostatistics for subsequentlymapping the spatial variability of these parameters. The results show that the altitude (m) and meanannual temperature (ºC) had low values for nugget effect (C0) while the annual precipitation (mm)had a larger value for this parameter. The mean annual temperature (ºC) and mean annual precipitation(mm) indicated data periodicity, detected by the experimental semivariogram. The spatial distributionmaps clearly show the influence of altitude on the values estimated by the kriging procedure for meanannual temperature (ºC) and mean annual precipitation (mm)